Increasing Teacher Sd Negeri 011 Kepenuhan Creativity And Initiative Through Online Learning Model During The Covid-19 Pandemic - Nismawati Nismawati (STKIP Rokania Pasir Pangaraian, 2021)
This study aims to determine the online learning model in increasing the creativity and initiative of teachers in managing learning at home at SD Negeri 011 Kepenuhan. The type of research conducted is school action research (PTS) using Elliot's model. The research was held at SD Negeri 011 Kepenuhan in the 2020/2021 academic year during the Covid 19 pandemic. The research subjects were grade 1, 2, 3, 4 and 5 teachers. The object of the research was learning at home through online learning during the COVID-19 pandemic. 19. Data were collected through observation and documentation and analyzed qualitatively. The results of this study indicate that the online learning model can overcome the implementation of learning during the COVID-19 pandemic through the creativity and initiative of teachers in managing learning at home. The creativity and initiative of teachers has increased in making lesson plans by 18%, online learning management by 12%, student activity by 17% and student learning scores by 9.6% from cycle I to cycle II in learning. After there is an active, creative and initiative teacher competency action in carrying out home learning, learning can run smoothly in dealing with the COVID-19 pandemic outbreak..